Using of Technology in the Formation of Creative Competence - Morkhova, Inessa VyacheslavovnA (International Journal of Psychosocial Rehabilitation, 2020)
This article was written with the aim of dvelopment the technology of forming the creative competence of a future teacher. In accordance with the purpose of the study, the research objectives are defined: to analyze and summarize the historical and pedagogical domestic and foreign experience and the current state of the problem of improving the technology of creative competence of a future teacher, also to improve the typology of teachers in terms of the level of creative approach to the student’s creative development, to develop a system of innovative technology improvement modules the formation of creative competence of students; substantiate the need for qualitative formal and substantial changes in the course of general pedagogy at a pedagogical university, taking into account the creative nature of the teacher’s activities and experimentally confirm the effectiveness of the proposed system, introduce it into the practice of preparing a future teacher.